REALISASI PENDAPATAN ASLI DAERAH SEBAGAI ALAT UKUR EFEKTIVITAS KINERJA KEUANGAN PADA KANTOR DINAS SUMBER DAYA AIR, CIPTA KARYA DAN TATA RUANG PROVINSI SULAWESI SELATAN - Daryanti Daryanti; Maria Angelina Ua (AkMen JURNAL ILMIAH, 2019)
This research aims to determine the financial performance of the Water Resources, Office and the Layout of the Province of South Sulawesi by calculating Regional Original Incom from 2015-2017. The data used are secondary data obtained from the Departemen of Water, Resources and spatial planning of sout Sulawesi Province in the from of Regional Revenue budgets for the 2015-2017 fiscal year. The results of this study indicate that, the development of the effectiveness of financial management in the work of the copyrighted water resources and the layout of the south sulawesi province during the 2015-2017 fiscal year can be said to be effective, namely, having an average effectiveness ratio below 100%, which only reaches 97,16%.